An Experimental Analysis on the Moment Rotation of Beam-Column Connection using Cold-form Steel Section - Nadya, Rahima Ummi Kulsum; Usman, Fathoni (International Journal of Engineering and Technology, 2018)
A beam-column connection of cold-formed steel section was arranged as an isolated joint. An experimental testing has been done on the model specimen until the model reached its failure mode. The behaviour of the cold-formed bolted connection in the matter of its strength and stiffness of the steel connection was studied. In this study, gusset-plate and bolted angle flange cleat connection were used in which it can stiffen the cold-formed beam-column connection. Moment-rotation curves were generated from the test results to represent the behaviour of the bolted connections. The design expression of the beam-column connection is following the design standard of Eurocode 3 BS EN 1993-1-8. The set-up of the experimental analysis, the procedure and the failure mode results are discussed in details. The moment capacity of 5.9 kN.m has been recorded for the beam section and 7.3 kN.m for the column section. The stiffness (Sj) was recorded as 120.94 kN.m/rad for the beam section and 182.42 kN.m/rad for the column section.